Prevalence of Internet Addiction and associated risk factors in Jordanian school students. (May 2017) - Malak, Malakeh Z.; Khalifeh, Anas H.; Shuhaiber, Ahmed H.
Abstract: Internet Addiction has become a public health issue that cannot be neglected. In Jordan, there is a need to investigate this issue among school students. This descriptive correlational study aimed to assess the prevalence of Internet Addition and associated risk factors in Jordanian school students. The participants (N = 716) aged 12–18 years were selected randomly from ten public schools in Amman Governorate in Jordan. Socio-demographical data, patterns of Internet usage, the Young's Internet Addiction Tool (YIAT), the Symptom Checklist-anxiety scale (SCL-anxiety), and the Center for Epidemiological Studies Depression Scale for Children (CES-DC) were used. The findings showed that the prevalence of severe Internet Addiction was 6.3%. The highest prevalence of Internet Addiction was among students with family monthly income >1400/, their fathers completed elementary education and mothers completed university and higher education, and their academic performance was poor. The friend's home was the favorite place among Internet addicted students. Chatting was the highest reason for Internet Addiction. The students were experiencing anxiety and depression symptoms had the highest prevalence of Internet Addiction (10.3%, 8.2%, respectively). There was a statistically significant relationship between the age, school grade, family income, academic performance, average hours of Internet daily usage during school days and holidays, anxiety, depression, and Internet Addiction. These findings emphasize the importance of developing and implementing interventions such as preventive measures and early diagnosis of Internet Addiction among school students. Furthermore, counseling programs are recommended to increase the awareness of families regarding Internet Addiction and their responsibilities in providing guidance and support for their children. Highlights: Internet Addiction (IA) has become a public health issue that cannot be neglected. The prevalence of Internet Addiction was 6.3%. Age, school grade, family income, and academic performance were associated risk factors of IA. Duration of Internet daily usage, anxiety, and depression were also risk factors of IA. Developing and implementing interventions regarding IA among school students are essential.